Immunological and microbiological findings after the application of two periodontal surgical techniques: a randomized, controlled clinical trial. (22nd August 2013) - Kyriazis, Thomas; Gkrizioti, Sofia; Tsalikis, Lazaros; Sakellari, Dimitra; Deligianidis, Aristeides; Konstantinidis, Antonis
Abstract: Aim: To examine microbiological and immunological alterations following two periodontal surgical techniques, over a 6‐month period. Materials and methods: A total of 30 chronic periodontitis patients participated in the present randomized controlled clinical trial and were randomized in two groups. Modified Widman flap (MWF) was applied in the control group and apically positioned flap (APF), without intervention to the bone, in the experimental group. Gingival crevicular fluid samples and subgingival plaque samples from the operated sites were collected at baseline, 6th, 12th and 24th post‐operative week. Results: No major differences were noticed in immunological and microbiological profile of patients receiving either modified MWF or APF, for a period of 6 months. Conclusions: The choice of the periodontal surgical procedure does not seem to affect the immunological and the microbiological profile of patients with chronic periodontitis.